PENGARUH PEMANFAATAN MEDIA DIGITAL INTERAKTIF TERHADAP MOTIVASI DAN HASIL BELAJAR EKONOMI SISWA SMA NEGERI 8 KOTA TERNATE DALAM KONTEKS KURIKULUM MERDEKA - Febiyanti Umaternate; Nadila Rumbou; Ode Zulaeha (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This study is motivated by the need to improve the quality of economics learning in the digital era, particularly within the implementation of the Merdeka Curriculum, which emphasizes learner autonomy, creativity, and the use of technology as a supporting medium. The purpose of this research is to analyze the influence of interactive digital media utilization on students’ motivation and learning outcomes in economics at SMA Negeri 8 Kota Ternate. This research employs a quantitative approach with an ex-post facto design and survey techniques. The sample consists of tenth- and eleventh-grade students selected through proportional random sampling. The instruments used include a Likert-scale learning motivation questionnaire and a validated economics learning achievement test. Data were analyzed using multiple linear regression to examine the direct effect of interactive digital media on students’ motivation and learning outcomes. The findings show that the use of interactive digital media has a positive and significant influence on learning motivation and contributes strongly to the improvement of students’ economics learning outcomes. Furthermore, learning motivation is proven to mediate the relationship between the use of interactive digital media and students’ academic achievement. The study concludes that integrating interactive digital media into economics learning within the context of the Merdeka Curriculum creates a more engaging, independent, and effective learning experience for students at SMA Negeri 8 Kota Ternate.